Implicit theories of self-regulated learning: interplay with students' achievement goals, learning strategies, and metacognition - Hertel, Silke; Karlen, Yves (British journal of educational psychology, 2021)
Background Implicit theories are important belief systems that influence an individual's motivation and behaviour. In academic contexts, domain-general implicit theories of ability (e.g., intelligence) and their relation to self-regulated learning (SRL) have been examined. Aims In this study, we followed a domain-specific approach and first introduced scales to assess students' implicit theories of the malleability and of the relevance of SRL. Second, we investigated how implicit theories of SRL are related to students' SRL. Third, we examined the relationship of implicit theories of SRL with students' demographics and personality traits. Sample Participants were students from a medium-sized university in Germany (N = 254) aged M = 23.85 years. Methods Data on students' demographics and personality traits, implicit theories of intelligence (INT), achievement goals, and learning strategies were collected with well-established measures. In addition, students' implicit theories of SRL and their declarative metacognitive knowledge about SRL were assessed with measures developed within this study. Confirmatory factor analyses and regression analyses were performed. Results The two postulated dimensions of implicit theories of SRL were supported. As expected, implicit theories of SRL were more strongly related to students' achievement goals, learning strategies, and metacognitive knowledge than implicit theories of INT. Moreover, implicit theories of SRL were mostly unrelated to students' demographics and personality traits. Conclusion The results emphasize that domain-specific implicit theories of SRL contribute substantially to the explanation of students' SRL. Thus, further research on SRL should consider domain-specific implicit theories of SRL in addition to implicit theories of INT.